Unemployment, Cost and Availability of Accommodation and Wage Changes in Ontario - Della Valle, P.; Green, R. (Relations industrielles / Industrial Relations, 1970)
The purpose of this paper is to determine whether there are consistent and significant relationships between wages changes, unemployment and cost and availability of accommodation in urban areas in Ontario.